(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
With Love, From Inside is an original play created by the Dropped Keys Theatre Company, composed of theater students from the University of Michigan (U-M) and writers and performers who are survivors of incarceration or currently incarcerated. The production originated from the students’ regular visits to prisons to facilitate theatrical workshops. The play’s program states that it is a response to the sadness felt by the students upon realizing that many people in the outside world will never meet the extraordinary individuals living behind walls. Thus, the life stories, love, pain, humor, and survival of these individuals are presented. The audience is then presented with a dramaturgy-as-a-letter, a call to write about other worlds where these encounters may take place through the materialized word.